A Case report on Pemphigus Vulgaris (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2024)
Pemphigus Vulgaris (PV) is a chronic auto immune bullous dermatosis. It is the most frequent and severe form of pemphigus occurring universally between 40 and 60 years of age. It is a life-threatening sickness causing blisters and erosions on the oral mucosa followed by lesions on the other mucous membranes and flaccid blisters on the skin, which can be disseminated. The underlying mechanism involves binding of immunoglobulin G auto anti-bodies to desmoglein (Dsg) 1 and 3, a transmembrane glycoprotein adhesion molecule present on desmosomes. Here a 47 years old male patient admitted in the Department of Dermatology with a chief complaint of multiple fluid filled lesions along with erosions present all over the body in the last 3 days. His past medical history revealed that he was suffering from this problem since one and half year and on corticosteroid medication, which provided temporary relief. The patient condition was not improved with the administration of corticosteroids but there may be a chance of improvement, if the treatment strategy was changed.